A Required, Combined Neurology-Physical Medicine and Rehabilitation Clerkship Addresses Clinical and Health Systems Knowledge Gaps for Fourth-Year Medical Students. (February 2021) - Curtis, Caitrin M.; Eubanks, James E.; Charles, Stephen C.; Boyer, Philip J.; Harrell, Kelly M.; Markandaya, Manjunath; Lawson, Luan E.; Norbury, John W.
Abstract : Abstract: This study evaluated the impact of a 4-wk mandatory neurology-physical medicine and rehabilitation advanced-core clerkship for fourth-year medical students. The combined clerkship encouraged an interdisciplinary and function-based approach to the management of common neurologic, musculoskeletal, and pain complaints. Seventy-three fourth-year medical students participated in the rotation over 1 yr. A survey assessing knowledge and skill set topics was conducted before and after the clerkship. Qualitative feedback regarding the rotation was provided by the students and analyzed. Significant gaps in knowledge and skill sets were identified before the clerkship and successfully addressed by combined teaching modalities. These data demonstrate that an integrated neurology-physical medicine and rehabilitation clerkship can improve students' confidence in multiple domains. Integrating physical medicine and rehabilitation into core clerkships at other medical schools may provide an avenue to address curriculum gaps.